Pengukuran tahap kepuasan pelanggan dalam industri perkilangan . Kajian kes di Amcor Fibre Packging (M) Sdn Bhd Senai Johor. - Ee, Khor Chen (2004)

(untitled)
Customer Satisfaction is one of the most important factors to decide the achievement of the companies whether in manufacturing industry or servicing industry, especially nowadays, the competition become tougher in the business sector. This issue causing many of the organizations starts to put more efforts and methods to enhance the customer satisfaction in order to increase the profit margin and reputation of the organization. This research carried out is to know more regarding the measurement of the customer satisfaction in terms of customer service in manufacturing industry which is Amcor Fibre Packaging (M) Sdn Bhd in Senai, Johor. The purposes of this research are to measure the customer satisfaction level within the organization in terms of customer service, relationship between respondent backgrounds which include organization sizes, period of respondent become customer and customer satisfaction and the relationship between each level of the customer satisfaction. Total of 93 respondents which also the organization existing customers are involved and questionnaires have been used in this research. All the data collected in quantitative forms were analyzed by using SPSS software version 11.0. Result of the research indicates that only the product or service dimension has achieved customer expectation. However, other dimensions such as process and support dimension, technical performance dimension, customer interaction elements dimension and emotional elements dimension were not achieved the expectation. In addition, result shows that there is the positive relationship between organization size and customer satisfaction and there is no relationship between periods of respondent become customer and customer satisfaction. Finally, a few proposals have been proposed to management and academician to solve the said problems.